Current medical diagnosis & treatment study guide - Quinn, Gene R. (McGraw-Hill Education/Medical, 2014)
Provides an organized synopsis of each topic, making it an essential study partner for a variety of examinations, including the USMLE Step 2, medicine clerkship shelf exams, ABIM internal medicine boards and recertification exams, adult and family nurse practitioner certification examination, and physician assistant national certifying exam.